Biotin Synthesis in Plants. The First Committed Step of the Pathway Is Catalyzed by a Cytosolic 7-Keto-8-Aminopelargonic Acid Synthase - Pinon, Violaine (American Society of Plant Biologists, 2005)
Biochemical and molecular characterization of the biotin biosynthetic pathway in plants has dealt primarily with biotin synthase. This enzyme catalyzing the last step of the pathway is localized in mitochondria. Other enzymes of the pathway are however largely unknown. In this study, a genomic-based approach allowed us to clone an Arabidopsis (Arabidopsis thaliana) cDNA coding 7-keto-8-aminopelargonic acid (KAPA) synthase, the first committed enzyme of the biotin synthesis pathway, which we named AtbioF. The function of the enzyme was demonstrated by functional complementation of an Escherichia coli mutant deficient in KAPA synthase reaction, and by measuring in vitro activity. Overproduction and purification of recombinant AtbioF protein enabled a thorough characterization of the kinetic properties of the enzyme and a spectroscopic study of the enzyme interaction with its substrates and product. This is the first characterization of a KAPA synthase reaction in eukaryotes. Finally, both green fluorescent protein-targeting experiments and western-blot analyses showed that the Arabidopsis KAPA synthase is present in cytosol, thus revealing a unique compartmentation of the plant biotin synthesis, split between cytosol and mitochondria. The significance of the complex compartmentation of biotin synthesis and utilization in the plant cell and its potential importance in the regulation of biotin metabolism are also discussed.